(untitled) (International Journal of Psychosocial Rehabilitation, 2020)
The project Hospital Management system includes patients registration, storing their data into the system database and appointment process. The software also has the facility to generate a unique id patient and stores the data of each and every patient, staff and doctor. The receptionist can know the patients details based on the unique id and the doctors’ availability in a particular day. The software is accessed by the admin and also users can access by username and a password given by the admin. The data can be added, updated, deleted and retrieved easily. A user-friendly interface has been designed and the data is also protected. This software is build using ServiceNow platform. ServiceNow is a cloud-based software platform which supports ITSM. It enables to automate IT Business Management (ITBM). It offers power, flexibility and dependability to achieve the objectives of the incident and problem management.